Phase transformations in an Aurivillius layer structured ferroelectric designed using the high entropy concept. (1st May 2022) - Zhang, Man; Xu, Xinzhao; Ahmed, Shafique; Yue, Yajun; Palma, Matteo; Svec, Peter; Gao, Feng; Abrahams, Isaac; Reece, Michael J.; Yan, Haixue
Abstract: A single phase four-layer Aurivillius structured ferroelectric ceramic, (Ca0.2 Sr0.2 Ba0.2 Pb0.2 Nd0.1 Na0.1 )Bi4 Ti4 O15 (6ABTO) was obtained using a high entropy design concept. The material, which has orthorhombic symmetry in space group A 21 am at room temperature, has Ca 2+, Sr 2+, Ba 2+, Pb 2+, Nd 3+ and Na + distributed not only on the A sites of the perovskite layer but also in the bismuthate layer. 6ABTO shows complex ferroelectric behavior, with a Curie point of 557 °C. Four current peaks are observed in the current - electric field curve. These peaks are attributed to a combination of a field induced phase transition and domain wall switching, which is the first reported occurrence of such current - electric field behavior for an Aurivillius structured ferroelectric material. Despite the level of disorder between the A site cations in the perovskite layer and the Bi positions in the bismuthate layer, 6ABTO does not show the relaxor ferroelectric behavior, that is commonly observed in cases of such disorder. This suggests that relaxor behavior in ferroelectrics, may be more associated with the thermal stability of dipoles, rather than the presence of polar nano-regions formed as a result of chemical disorder. The nature of the high entropy effect in 6ABTO is discussed through comparison of results from isostructural compositions containing 5, 4 and 3 of the component cations Graphical Abstract: Image, graphical abstract